GAMILAB: it's not just about games! / Noor Shahariah Saleh and Nurul Syafawani Halim - Saleh, Noor Shahariah; Halim, Nurul Syafawani (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Amidst the Covid-19, online distance learning (ODL) is no longer considered novel in higher institutions. With this sudden shift away from the physical classroom to virtual space, some are wondering whether the adoption of this online learning will continue to persist post-pandemic, and how such a transformation would impact the worldwide education market. However, the imposition of ODL sessions for three semesters in a row has already raised red flags among Malaysian university lecturers and students. It appears that instructors are losing students' interest and involvement, while students find online learning laborious and time-consuming. To deal with the dilemma, educators should devise new ways to make learning more exciting and enjoyable.